Critical exponents and universal magnetic behavior of noncentrosymmetric Fe0.6Co0.4Si. (2nd May 2018) - Samatham, S Shanmukharao; Suresh, K G
Abstract: The critical magnetic properties of a non-centrosymmetric B20 cubic helimagnet Fe0.6 Co0.4 Si are investigated using magnetization isotherms. It belongs to the 3D-Heisenberg universality class with short range magnetic coupling as inferred from the self-consistent critical exponents, , and in combination with exchange interaction . Itinerant magnetic nature of the compound is realized by the Rhodes–Wholfarth analysis. Field-induced weak first (para helical) to second (para field-polarized) order transition is reported to occur at low critical field due to the weak spin–orbit coupling arising from the weak Dzyaloshinksii–Moriya interactions. Our study suggests the distinct phenomenological magnetic structures for Fe-based cubic magnets (Fe1− x Co x Si and FeGe) and MnSi which cause contrasting physical properties.